2013
DOI: 10.1111/tbj.12077
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mismatch Repair Protein Expression in Breast Carcinoma in Patients with Lynch Syndrome: Report of Two Cases

Abstract: Lynch Syndrome, an autosomal dominantly inherited cancer predisposition syndrome is not typically associated with development of breast cancer. We present two cases of loss of mismatch protein expression in breast cancer cases in patients with Lynch Syndrome and discuss the literature surrounding the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Even though the risk of breast cancer in Lynch syndrome remains controversial, growing evidence supports that monoallelic mutations in certain MMR genes are associated with an increased breast cancer risk [17][18][19][20][21]. Shlien et al first identified the ultra-hypermutated phenotype in brain tumors of children with CMMRD [10] and the sister's ultra-hypermutated glioblastoma showed the highest mutational burden documented in literature to the authors' knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the risk of breast cancer in Lynch syndrome remains controversial, growing evidence supports that monoallelic mutations in certain MMR genes are associated with an increased breast cancer risk [17][18][19][20][21]. Shlien et al first identified the ultra-hypermutated phenotype in brain tumors of children with CMMRD [10] and the sister's ultra-hypermutated glioblastoma showed the highest mutational burden documented in literature to the authors' knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that this premalignant lesion related to LS tends to undergo more rapid development in LS patients than in patients who do not have LS [ 7 , 8 ]. According to the pathological characteristics of LS, a high degree of lymphocyte infiltration is often observed in the cancer tissue, with the tumors being poorly differentiated and mucinous and/or comprising signet ring cell carcinoma [ 2 , 5 , 12 ].…”
Section: Case Presentationmentioning
confidence: 99%